Neo-orientalist narratives - Makram, Mohammad; Quayum, Mohammad Abdul (IIUM Press, International Islamic University Malaysia, 2017)
Critics such as Edward W. Said and others have noticed a tendency among some Western and pro-Western writers to reproduce the Orientalist discourse in the aftermath of the 9/11, 2001 attacks, which they describe as neo-Orientalism. This book attempts to examine the writings of four writers, Åsne Seierstad (1970-), Khaled Hosseini (1968-), Azar Nafisi (1958-) and Denis MacEoin (pen-name Daniel Easterman) (1949-) to investigate how they represent Muslims and Muslim societies in their work. It attempts to investigate if they reproduce the Orientalist discourse, and employ it to justify and instigate contemporary imperialism. Analytical, comparative and historical methodologies have been used to answer the research questions. All the writers studied in this book have shown, although in different degrees, signs of reproducing the Orientalist discourse. The findings of this research may help to understand what neo-Orientalism in literature is and how to encounter its negative impact on the relationship between the Muslim World and the West. However, this book is not limited to merely criticising neo-Orientalism. It proposes a different worldview based on the tenets of the Holy Qur’an to replace hostile and self-isolating discourses such as Orientalism, which the book terms as the Qur’anic Worldview.